Sleep, Sleepiness, and Memory - Bianca Estefani Schmidt; Lucas Henrique Lopes-de-Souza; Athany Gutierres; Tiago Teixeira Simon (Sleep Science)
Objective To evaluate the relationship between sleep and sleepiness with memory complaints.